Konsep Keuangan Publik dalam Pemikiran Abu ʿUbaid al-Qāsim ibn Sallām: Analisis Kitāb al-Amwāl dan Relevansinya bagi Ekonomi Islam Kontemporer - Ghilman Nursidin Syarief (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the concept of public finance formulated by Abu ʿUbaid al-Qāsim ibn Sallām in Kitāb al-Amwāl and analyzes its relevance to contemporary Islamic public finance. Employing a qualitative library research approach, this study analyzes primary sources from Kitāb al-Amwāl alongside classical and contemporary literature on Islamic public finance, governance, and fiscal policy. The analysis demonstrates that Abu ʿUbaid developed a comprehensive framework of public finance grounded in distributive justice, public accountability, transparency, and state responsibility for social welfare. Unlike approaches that merely emphasize state revenue, his framework integrates ethical, legal, and administrative dimensions into a coherent fiscal system. These principles remain highly relevant for addressing contemporary challenges, including inequality, corruption, inefficient public expenditure, and the integration of zakat into national fiscal policy. The findings suggest that Kitāb al-Amwāl should be understood not only as a historical legal text but also as an important normative reference for developing an ethical, accountable, and inclusive model of Islamic public finance capable of responding to modern governance challenges.